Variability of Essential and Nonessential Fatty Acids of Irish Rapeseed Oils as an Indicator of Nutritional Quality. (12th January 2022) - Coughlan, Rebecca; Moane, Siobhan; Larkin, Tracey
Abstract : The low saturated fatty acid content of rapeseed oil has resulted in it being classed as one of the most health-benefiting culinary oils. This study determines whether Irish rapeseed oils contain identical fatty acid profiles or whether distinct profiles exist between producers and producers' successive oil batches. The fatty acid content of Irish rapeseed oils was determined in terms of the desirable MUFA and PUFA and saturated content of these oils. The fatty acid composition demonstrated significant differences in individual unsaturated fatty acid content, while total saturation had insignificant differences. Saturated fatty acid content ranged from 6.10 to 15.8%, while unsaturated fatty acids ranged from 84.20 to 90.10%. Moreover, individual fatty acid content exhibited significant differences (p < 0.05 ). Oleic acid (C18:1), linoleic acid (C18:2), and stearic acid (C18:0) contents were considered significantly different from other fatty acids detected. The third successive batch from each producer exhibited lower oleic acid content, and the third batch contained higher linoleic acid content, at the same time maintaining a desirable unsaturated fatty acid composition. Studies suggest that differences in the fatty acid composition may be due to cultivation practices such as climate, soil composition, sowing and harvesting, processing techniques, and oxidation reactions.